Attitude of healthcare workers towards information technology - Dajana Milidrag; Aleksandar Tanović; Igor Medenica; Lado Davidović (Биомедицинска истраживања, 2024)
Introduction: Digital literacy includes things like being able to use information systems and supporting infrastructure. With the increasing use of technology in healthcare, it is important for healthcare staff to be digitally literate. The aim of the paper is to determine the attitudes of primary and secondary health care workers towards the use of computers in health care and to examine the influence of sociodemographic factors on the information literacy of health care workers. Methods: The research was conducted according to the principle of a cross-sectional study. The research included 80 respondents, healthcare workers. Data analysis included methods of descriptive and inferential statistics. The data will be presented in the form of a table. Results: The results showed that certain socio-demographic factors influenced the attitude of health workers towards the use of computers. The most significant factors were the level of education and previous IT education, but the time the respondents sopent working on the computer and whether they used the computer exclusively at work or at home also had an impact. Conclusion: Healthcare workers showed a positive attitude towards the use of computers in healthcare. The most significant socio-demographic factors influencing knowledge of computer work are the level of education of the respondents and whether and where they received their education in information technology.
Keywords: digital literacy; attitudes and factors towards information technology; information technology education in healthcare